2006
DOI: 10.1021/pr0605217
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Strategies in Metabonomics

Abstract: To perform metabonomics investigations, it is necessary to generate comprehensive metabolite profiles for complex samples such as biofluids and tissue/tissue extracts. Analytical technologies that can be used to achieve this aim are constantly evolving, and new developments are changing the way in which such profiles' metabolite profiles can be generated. Here, the utility of various analytical techniques for global metabolite profiling, such as, e.g., 1H NMR, MS, HPLC-MS, and GC-MS, are explored and compared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
417
0
15

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 495 publications
(441 citation statements)
references
References 128 publications
1
417
0
15
Order By: Relevance
“…Both methods enable the comprehensive investigation of metabolic profiles (Dunn et al 2005, Hollywood et al 2006, Lenz & Wilson 2007 and can provide complementary snapshots of the metabolome of body fluids such as plasma, urine or cerebrospinal fluid (Bictash et al 2010).…”
Section: Metabolomics Technologiesmentioning
confidence: 99%
“…Both methods enable the comprehensive investigation of metabolic profiles (Dunn et al 2005, Hollywood et al 2006, Lenz & Wilson 2007 and can provide complementary snapshots of the metabolome of body fluids such as plasma, urine or cerebrospinal fluid (Bictash et al 2010).…”
Section: Metabolomics Technologiesmentioning
confidence: 99%
“…If the correlation value of two mass spectra is lower than the threshold, the pair is classified as negative. After the calculation of the correlation value for every pair of spectra, we can obtain TPR and FPR for a given threshold using the following, (9) where TP (true positive) is the number of positive pairs that were classified as positive, FN (false negative) is the number of positive pairs that were classified as negative, FP (false positive) is the number of negative pairs that were classified as positive, and TN (true negative) is the number of negative pairs that were classified as negative. While changing the threshold value from −1 to 1, we calculated the values of FPRs and TPRs, where each pair of (FPR, TPR) corresponds to a specific threshold value.…”
Section: Analysis Of Data Generated From Standard Metabolite Mixturesmentioning
confidence: 99%
“…Although the number of known metabolites in many organisms is fewer than the number of genes or proteins, development of profiling methods and analytical techniques for metabolite detection and identification is a challenge due to the chemical diversity of metabolites and large concentration ranges. Many analytical techniques have been applied in metabolomics including liquid chromatography (LC), capillary electrophoresis (CE), gas chromatography (GC), and each of these coupled with mass spectrometry (LC-MS, CE-MS and GC-MS) [5][6][7][8][9]. Single dimension methods however, often provide discriminating capability that is too limiting.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many platforms for metabolic profiling (for example, LC-MS, GC-MS, NMR, electrocapillary phoresis-MS), no one technology gives complete coverage of the metabonome. This technique has been used extensively in studies on schizophrenia, [16][17][18][19] Alzheimer's disease, 20 Huntington's disease, 21 Batten disease 22 and human brain tumors 23 (for detailed reviews on metabonomics, see Holmes et al 24 and Lenz and Wilson 25 ). These studies have identified a number of biochemical alterations that may be occurring as part of the pathogenesis of these diseases.…”
Section: Introductionmentioning
confidence: 99%